Tennis Club Nettings, volume 12, no. 7, May 1974 (The Tennis Club, 1974)
The magazine for May 1974 discusses the easter brunch, the Monte Carlo ball, and the Polynesian party that took place at the Tennis Club. The magazine highlights the Palm Springs Academy of Medicine's tennis competition, celebrity golf, and fishing and hunting opportunities in the area.